Finding the link between internalized weight-stigma and binge eating behaviors in Portuguese adult women with overweight and obesity: The mediator role of self-criticism and self-reassurance. (August 2017) - Palmeira, Lara; Pinto-Gouveia, José; Cunha, Marina; Carvalho, Sérgio
Highlights: Weight self-stigma was positively correlated with self-criticism and binge eating. Weight self-stigma was negatively associated with self-reassurance. Significant differences between women with and without BED were found. Self-criticism and self-reassurance are relevant processes in binge eating symptoms. Clinical interventions should focus on the development of self-compassion skills.